Physical profile of elite young motorcyclists - Sanchez-Munoz, C.; Rodriguez, M. A.; Casimiro-Andujar, A. J.; Ortega, F. B.; Mateo-March, M.; Zabala, M. (International Journal of Sports Medicine, 2011)
The aim of the study was to describe anthropometric and physical characteristics of elite young road-race motorcyclists (MC). 27 riders (15.6±1.1 years, 54.6±6.9 kg, 166.9±6.7 cm) competing at international elite level participated in this study. Anthropometric variables, hand grip and lumbar isometric strength, and lower-body muscular strength were measured. Comparisons of the MC and a reference group of Spanish physically active adolescents (16.0±0.6 years) showed that the riders were significantly lighter (-12.5 kg), and smaller (-4.7 cm). Riders also had significantly lower values for almost all skinfolds, and for all the measured girths (except forearm) than the reference group. Motorcyclists showed significantly less percent body fat (%BF) and higher muscle mass, and differences were observed for somatotype components compared to the reference group, except for the ectomorphy. Somatotype could be defined as mesomorphic-ectomorph (2.5-4.4-3.7). Mean (±SD) values of all riders were 34.8±5.0 cm for vertical jump height, 402.1±74.5 N for the right hand and 370.7±77.5 N for the left hand strengths, and 120.6±19.3 kg for lumbar isometric strength, respectively. Results demonstrate that MC are small and light, with lower body mass index, skinfolds, girth and breadth dimensions, and %BF than a reference group and other athletes, with high values of hand grip and lumbar isometric strength.